Peadiatric amputation from traditional bone setters’ gangrene in Ibadan: a malady - Balogun, Mosimabale J.; Morhason-Bello, Jemiludeen O.; Olusola, Idowu K. (International Journal of Research in Orthopaedics, 2024)
Background: Pediatric amputations resulting from gangrene pose a significant medical challenge, especially in resource-limited settings. In Nigeria, traditional bone setters (TBS) often serve as the first point of contact for musculoskeletal injuries, but their practices can lead to severe complications, including gangrene. Our hospital manages many of such cases. This study aims to explore the epidemiology, clinical presentation, and outcomes of pediatric patients who developed gangrene requiring amputation following TBS treatment, with the goal of informing public health strategies and improving pediatric care quality. Methods: The study is a retrospective study which seek to extract the data from the hospital record all the patient who underwent amputation due to gangrene after initial TBS treatment. All the case notes were retrieved and data was extracted and analyzed using descriptive statistics. The study adhered to ethical standards and anonymized data to protect patient confidentiality, ensuring the study’s integrity. Results: The study involved 33 pediatric patients aged 8.3 years, with a significant gender disparity. Most patients were from the Yoruba ethnic group and practiced Islam. 87.9% of parents had no formal education. Gangrene was most common in the left hand, and falls were the leading cause of initial injury. The average surgery time was 81.2 minutes, with a 13-day hospital stay. Post-operative complications occurred in 43.5% of patients, with surgical site infections (SSI) being the most common. Only 8.7% received occupational therapy. Conclusions: The study highlights post-operative care challenges in pediatric amputations, including high complications and limited access to services. It suggests targeted interventions, infection control, and public health campaigns to improve outcomes. Future research should include long-term follow-up studies.